GAMBARAN MANAJEMEN PENGELOLAAN LIMBAH PADAT DI HEALTH CENTRE PERUSAHAAN X LAMPUNG TENGAH - Dwi Lassmy Samaritan; Surahma Asti Mulasari (Medika Respati : Jurnal Ilmiah Kesehatan, 2015)
Background : Management of solid waste consists of medical solid waste and non-medical solid waste. Medical solid waste and non-medical solid waste hospital is necessary for the comfort and cleanliness of the hospital, because it can break the chain of spread of infectious diseases, especially nosocomial infections. Issues contained in solid waste management, namely: distance hospitals and waste management much so that there should be a conditioning at polling stations, there are several shelters waste is not closed, there is no evaluation at the hospital about the number of bacteria at the pooling station and pest control. The purpose of this study was to describe the management of solid waste management in the Health Centre X Company Central Lampung.Methods : This study was a qualitative descriptive study, the subjects in this study was in charge of waste management Health, head of executors, Health Officer, Staff Research. Research tools using methods of observation and in-depth interviews. Data analysis was performed by descriptive qualitative, to ensure the validity of the data, the data collection techniques using triangulation techniques.Results : Based on the results of research using the method of observation and in-depth interviews showed that the management of solid waste management is already well underway, medical waste generated very little so it does not require a lot of human resources to manage it. Human resource needs are fulfilled visible from the neat bins and emptied on time, facilities and infrastructure already available in some detail with the support of the X Company Central Lampung, the system of cooperation with LB3 good enough for the effectiveness and efficiency of the management of medical waste by combining the waste with RS X, solid waste management is quite in accordance with KEPMENKES 1204/2004.Conclusions : Management of solid waste management has been going well. Medical waste generated very little. Resource requirements have been fulfilled. Facilities and infrastructure already available in some detail. The system of cooperation with LB3 good enough for effectiveness and efficiency. Solid waste management is quite in accordance with KEPMENKES 1204 2004. Keywords : Management, Execution, Solid Waste, Medical Waste, Non-Medical Waste